Digital Pathology, A Cognitively Efficient Teaching Strategy: Current Application and a Glimpse into Future. (9th November 2022) - Saxena, R; Moore, N; Johnson, J
Abstract: Introduction/Objective: If pathology education is to be efficacious, it must embrace the ramifications of cognitive load of the learners, to optimize the capacity of the working memory. When undergraduate students commence their learning of pathology, they encounter a heap of new data and classifications. Simplifying these intricate systems into assimilable subschemas and items is key for effective transfer of knowledge. The minimization of the profundity of intrinsic cognitive load is essential, considering that its impact on pathology beginners is often left unaccounted, both in active learning as well as in traditional methods of instruction. In today's digital generation, digital pathology plays a key role by intertwining disease morphology with clinical presentation and fortifying its pathophysiologic basis. We designed a teaching methodology utilizing digital pathology to evaluate its effect on cognitive load. Methods/Case Report: Active learning was implemented online using digital pathology, molecular pathology, and laboratory data in case-based setting with question-answer sessions. In small groups, students were encouraged to analyze digital pathology slides with the help of annotations and identify areas of histopathological significance. They utilized this information further to make an accurate diagnosis and answer corresponding questions, with access to answers available later, complemented with algorithms and concept maps. A 14-item structured questionnaire was delivered afterwards to evaluate the efficacy and popularity of the exercise. Results (if a Case Study enter NA): End-of-term examination results showed that learners developed higher-order comprehension skills along with a greater potential in interpreting histopathological data towards solving case studies. Feedback revealed a higher degree of overall satisfaction and increased ability to retain information. Conclusion: Digital transformation of pathology education provides the kind of framework where learning happens naturally - developing in small boosts of progress until expertise is achieved, and students appreciate the value of the 'learned thing' along with the real utility of that knowledge. The innovative approach utilizing digitization and integration offers the opportunity of decrement in intrinsic cognitive load by invoking students to build better, reliable, long-lasting, supportable and inclusive schemata while correlating the relevant incoming information with previously stabilized knowledge and consolidating the entirety of understanding.